LEGALITAS SISTEM MONETISASI LOOTBOX DALAM TRANSAKSI GAME ONLINE BERDASARKAN UNDANG-UNDANG NOMOR 11 TAHUN 2008 JO UNDANG-UNDANG NOMOR 19 TAHUN 2016 - Muhammad Theo Rizki Putra; Ariawan Gunadi (Fakultas Hukum Universitas Tarumanagara, 2020)
The advancements in technologies of the current world has given birth to many new services for daily consumption and the general betterment of quality of life. These services can be in the form of recreational applications, also known as video games. One of the monetization system used by the video games industry is lootbox monetization system, a system where consumer can buy a lootbox containing of randomized virtual items using real money or other currencies and has raised concerns about the legality of such practices in the eyes of Indonesian laws. How is the legality of this lootbox monetization system according to Act 19 Year 2016 jo Act 11 Year 2008? How responsible is the goverment towards the negative influences and effects of lootbox monetization system? This journal is written using the normative research method. The research data shows that lootbox monetization system has inherent gambling elements and negative influences, but legally still in the grey area of the law. These gambling elements are illegal in the eyes of Indonesian laws and regulations The goverment has to conduct a legal research on lootbox monetization system, and to regulate such practices in Indonesia.